Lithuanian Discourse Markers And Their Relations In A Multilingual Corpus - Oleškevičienė Giedrė Valūnaitė; Karaciejūtė Vitalija; Gulbinskienė Dalia (Darnioji daugiakalbystė, 2023)
The development and research of discourse-annotated corpora is a relatively new field, therefore Lithuanian researchers seek to supplement the existing corpora resources and look for ways to study discourse relations by linking and comparing them with their counterparts in other languages because in different languages discourse relations are realized by different linguistic means. The aim of the article is to present the developing available corpora resources drawing on the experience of foreign scholars and to discuss guidelines for translation research at the discourse level. Therefore, the article first deals with the possibilities of expressing discourse relations by using discourse markers as their linguistic realization in different languages, discussing possible choices of translators, taking into account discourse realtions in translation and the use of different linguistic means. The article presents the parallel multilingual corpus TED-MBD (Multilingual discourse-annotated corpus), which is annotated at the discourse level, in accordance with the objectives and principles of PDTB (Penn Discourse Treebank) discourse annotation. The article discusses in detail the annotation system of PDTB discourse markers, the reader is introduced to the hierarchy of senses of discourse relations, the principles of annotation and insights into the application of the PDTB scheme. It also describes the annotation principles of the Lithuanian part of the corpus in accordance with the PDTB discourse annotation rules; the first results related to the expression of discourse relations and the use of discourse markers are discussed. The article also presents the first research guidelines on how to compare Lithuanian and English discourse-annotated texts in order to understand translation tendencies at the discourse level.